PEMANFAATAN BASIS DATA GEOGRAFIS DALAM MENGEMBANGKAN PARIWISATA DI KABUPATEN KARO - Arie Satria Tama; Muhammad Irwan Padli Nasution (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research is entitled Utilization of Geographical Databases in developing Tourism in the Tourism Area of ​​Karo Regency, North Sumatra Province. To assist the North Sumatra Province Culture and Tourism Office in promoting tourism in Karo Regency, it is hoped that the number of domestic and foreign tourists visiting Karo Regency will increase, increasing the income of the surrounding community. By using the Google Maps API, this research uses digital maps that display names, photos, descriptions and locations of tourist attractions taken from the Google DBMS database. The aim of this research is to increase the possibility of tourists from North Sumatra Province visiting Karo Regency. Because North Sumatra has a lot of tourism potential, one of which is Karo Regency which has natural beauty and cultural diversity which is maintained by its people.